Occupational and Functional Outcomes following Patellofemoral Arthroplasty in U.S. Military Servicemembers - Fisher, Tuesday F.; Rider, Danielle E.; Waterman, Brian R.; Belmont, Philip J. (The Journal of Knee Surgery, 2023)
The functional outcomes in patients undergoing patellofemoral arthroplasty (PFA) with high occupational demands have not been fully examined. This study assessed return to work and conversion to TKA rates following PFA in a young, military cohort. Patient demographics, pain scores, and surgical information were retrospectively collected for all active-duty military members who underwent PFA over a 4-year period. The data were then analyzed to calculate return to work, conversion to TKA, and perioperative complications rates. A total of 48 servicemembers with 60 total PFAs (36 unilateral, 12 bilateral) were included, with a mean follow up of 2.2 years. At the final follow-up, 83% of servicemembers returned to military service or completed their service obligation after PFA. Conversion to TKA occurred in three (6.2%) patients at an average of 2.4 years after PFA, resulting in a PFA annual revision rate of 2.3%. The mean numeric rating scale for pain improved from 4.9 ± 2.6 at baseline to 2.5 ± 2.0 postoperatively (p < 0.001). Servicemembers with at least one prior ipsilateral knee procedure had a significantly decreased odds ratio (OR) for both occupational outcome failure (OR, 0.03; 95% confidence interval [CI], 0–0.29) and overall failure (OR, 0.13; 95% CI, 0.02–0.78). At an average of 2 years following PFA, 83% of military members returned to duty, with a low rate of revision to TKA. Prior ipsilateral knee procedure decreased the probability of medical separation.Level of Evidence IV
Keywords: patellofemoral arthroplasty; military; functional outcome; physical activity